Enhanced Time of Use Electricity Pricing for Industrial Customers in Malaysia - Nur Azrina Mohd Azman; Md Pauzi Abdullah; Mohammad Yusri hasan; Dalila Mat Said; Faridah Hussin (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
New Time of Use (ToU) tariff scheme known as Enhanced ToU (EToU) has been introduced on 1st January 2016 for industrial customers in Malaysia. EToU scheme is the advanced version of current ToU where the daily time frame is divided into six period blocks, as compared to only two in the existing ToU. Mid-peak tariff is introduced on top of peak-hour and off-peak tariff. The new scheme is designed to reduce Malaysia’s peak hour electricity demand. On customer side, they could be benefited from the low off-peak tariff by simply shifting their consumption. However, it depends on their consumption profile and their flexibility in shifting their consumption. Since EToU scheme is voluntary, each customer needs to perform cost-benefit analysis before deciding to switch into the scheme. This paper analyzes this problem by considering EToU tariff scheme for industry and customer’s electricity consumption profile. Case studies using different practical data from different industries are presented and discussed in this paper.